PENETAPAN KADAR FLAVONOID TOTAL EKSTRAK ETANOL DAN EKSTRAK ETIL ASETAT DAUN JELATANG (Urticadioica L.) SECARA SPEKTROFOTOMETRI-VISIBLE - Ahmad Gazali Sofwan; Yosy Cinthya Eriwaty Silalahi; Siti Nurbaya; Julianto Irawan (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
Nettle (Urticadioica L.) is a dicotyledonous plant in the Urticaceae family. The nettle plant contains flavonoids. The parts of the nettle plant used as medicine are leaves, roots, and seed stotreatvene real diseases, kidney disorders, allergies, diabetes, anemia, and digestivetract diseases. Nettle leaves contain a lot of secondary metabolites which are active compounds. The purposeofthis study was to determine the appropriate solvent used to obtain nettle leaf extract (Urticadioica L.) withthehighest flavonoid contentfro methanol extract and ethylacetate extract. Determination of total flavonoid contentfrome than olextract and ethylacetate extract of nettle leafe quivalent to quercetin (Quercetin Equivalent (QE)) using aluminum chloridereagentat a wave lengthof 437 nm by Visible spectrophotometry. Base don there search conducted and determined by visible spectrophotometry, the total flavonoid content of nettle leafe than olextract using aluminum chloridereagent was 322.2494 ± 49.2828 mg QE/g extract, whilethe total flavonoid content of nettle leafe thylacetate extract using aluminum chloridereagent was 254,3651 ± 15,0245 mg QE/g extract, The right solventused to obtain nettle leaf extract (Urticadioica L.) with the highest flavonoid contentis ethanol solvent.